Development of a Digital Career Literacy-Based Gamification Application to Improve Career Readiness of Students with Special Needs - Afriliyanto, Agus; Cahyaningrum, Vesti Dwi; Wulandari, Ratna; Da'i, Mohamad (Buletin Konseling Inovatif, 2025)
The development of digital technology has opened up new opportunities in education, including for students with special needs who often face obstacles in acquiring career skills, resulting in low career literacy and impacting their career readiness. This study aims to develop a digital career literacy-based gamification application as an innovative learning medium to improve the career readiness of students with special needs, with a scope covering design, development, and testing in accordance with their cognitive characteristics and learning needs. The study used a simplified Borg & Gall R&D model consisting of five stages, involving 30 students with special needs from inclusive schools in East Java, with instruments in the form of expert validation questionnaires, career readiness tests, and observations of student engagement. The results showed that the expert validation of the media obtained an average score of 88.5% (highly valid), the expert validation of the material was 91.2% (highly feasible), student engagement was 85%, and there was a significant increase in career readiness with an average pretest score of 62.4 to a posttest score of 82.7, or an increase of 32.5%. The digital career literacy gamification application has been proven to be valid, practical, and effective in improving the career readiness of students with special needs. Future research is recommended to involve a more diverse subject group and integrate adaptive technology for more optimal results.